2007
DOI: 10.1007/s00134-007-0670-7
|View full text |Cite
|
Sign up to set email alerts
|

Prone equals prone? Impact of positioning techniques on respiratory function in anesthetized and paralyzed healthy children

Abstract: Objectives: Although the prone position is effectively used to improve oxygenation, its impact on functional residual capacity is controversial. Different techniques of body positioning might be an important confounding factor. The aim of this study was to determine the impact of two different prone positioning techniques on functional residual capacity and ventilation distribution in anesthetized, preschool-aged children. Design: Functional residual capacity and lung clearance index, a measure of ventilation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…7 Lung volume and oxygenation increase due to improved ventilation/perfusion ratio in both adults and pediatric demographics. 7,15 Obese patients are at particular risk of increased abdominal pressure, increased venous pressure in the head, and decreased cardiac output and reduced end organ blood flow. 1,16 However, with proper supportive padding, these patients have better oxygenation in supported prone position versus supine position, as mediastinal contents fall anteriorly facilitating ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…7 Lung volume and oxygenation increase due to improved ventilation/perfusion ratio in both adults and pediatric demographics. 7,15 Obese patients are at particular risk of increased abdominal pressure, increased venous pressure in the head, and decreased cardiac output and reduced end organ blood flow. 1,16 However, with proper supportive padding, these patients have better oxygenation in supported prone position versus supine position, as mediastinal contents fall anteriorly facilitating ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with scoliosis are particularly difficult to position optimally because of anatomical distortion. A study by Von Ungern-Sternberg et al 16 compared the effects of "flat" and "augmented" prone positioning in children. The "augmented" prone position involved the use of supports for the pelvis and upper thorax.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, additional confounding factors, such as changes in ventilation distribution or differences in positioning techniques, might be important. In our recent study, we demonstrated that the augmented prone position (gel pads supporting the shoulders and the pelvis), in contrast to the flat prone position, increases FRC and thus could help to optimise respiratory function in paralysed, mechanically ventilated, healthy children [9].…”
Section: Impact Of Different Prone Positioning Techniquesmentioning
confidence: 98%